Determination of Midazolam in Animal Tissues by Solid-Phase Extraction HPLC-MS/MS Method - Zhao, Jianyuan; Zhao, Yan; Yang, Shuming; Zhang, Bin; Wei, Tao (Asian Journal of Chemistry, 2014)
Midazolam is usually used as ataractics for human. Addition of midazolam in animal feeds is forbidden by China Government for the health concern, however the residues of midazolam and its metabolites in animals can be inevitable found in food products that may cause drug resistance even have threaten to human health. On such basis, a reliable and sensitive method has been established and successfully applied for its determination in animal tissues by high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) analysis. Limit of detection of midazolam was 0.15 μg/kg and limit of quantification was 0.5 μg/kg. Midazolam was extracted from tissues samples with acetonitrile. The extract was purified by C18 solid phase extraction (SPE). The chromatographic separation was carried out on a C18 analytical column with a mobile phase composed of acetonitrile and 0.1 % formic acid. The presented method is sensitive and reproducible and thus suitable for accurate quantification of midazolam residue in animal-derived food products.